The social and economic impact of the Williamite war on Ireland, 1689-91 - Smyth, Alan J. (Trinity College (Dublin, Ireland). Department of History, 2013)
Events during the Williamite war in Ireland (1689-91) such as the siege of Derry, the battle of the Boyne and the signing of the treaty of Limerick, remain well-known incidents in popular Irish history, while the Jacobite defeat ensured the privileged status of Protestants in Ireland and subsequently enabled the passing of the Penal Laws. The main events and course of this important conflict have previously been well documented, but the more immediate impact of the war, specifically its social and economic effects on the general population, has remained largely unexplored. The initial outbreak of the war was in Ulster, and the motivation behind the armed resistance of the province's large Protestant population to James’s rule is assessed. Jacobite attempts to subdue these groups failed, and during their withdrawal from the siege of Derry they engaged in the deliberate destruction of property across central and southern Ulster. The civilians that remained in Derry during the siege endured significant hardship, resulting in various attempts to secure emergency supplies of food and fuel for the city and its environs. The arrival of a Williamite expeditionary force secured the province for the remainder of the war, although other problems remained, such as actions by rapparees and tensions between Williamite soldiers and the civilian population. The heightened religious tensions across Ireland during James's reign were particularly evident in Dublin city, where friction due to changes to the religious structures of society, such as the army and civic bodies, was evident on the city's streets. Eyewitness testimony details how these tensions were heightened with the outbreak of the war, as restrictions on Protestants gradually increased until the Jacobite defeat at the battle of the Boyne. Dublin was very fortunate to largely escape destructive military action or plundering following the battle, and the city came back into Williamite hands and under Protestant control. The impact of these transfers of power was a significant factor in the experience of the war for both Catholics and Protestants. Following the battle of the Boyne the Jacobite army and its supporters retreated towards Limerick, with poor discipline resulting in much plundering of civilians on the main routes to the city, as recorded in detail by members of the Quaker community. Detailed first-hand evidence such as this is quite rare, and their accounts are thoroughly assessed. For the remainder of the conflict the country was divided in two along the line of the river Shannon, and civilians living along this frontier saw significant hardship. This region bore a substantial burden of quartering troops from both sides, with associated frictions between soldiers and the civilians they were billeted with. The importance of this relationship between soldiers and civilians means it is investigated in depth, particularly during the long winter periods between campaigning seasons. The irregular forces known as rapparees were particularly active in this region, targeting Williamite soldiers, but also plundering civilians. Their composition, activities and motivations are assessed, as are the Williamite attempts to counter these rapparees, which resulted in further restrictions on ordinary Catholics, especially in these frontier areas. A major factor in civilians’ experience of the war was the overwhelming burden of having to supply these two large armies with food, supplies, horses and fodder, with the compulsory purchase of goods and other restrictions becoming commonplace. In the reduced Jacobite territory, primarily around Connacht, the impact was particularly severe. This resulted in high prices and food shortages, and the impact of the final year of the war in this area is examined from several perspectives. The extended impact of these various issues is assessed through the examination of various landed estates across the country, as landlords attempted to recover from the war’s adverse effects even prior to its conclusion. They were hampered by the destruction and dangerous environment caused by the conflict, which had driven many tenants from their homes and caused them to abandon their leases. The attempt by Derry corporation to use the positive view of their city’s contribution to the Williamite war effort as leverage to secure grants and help the area’s recovery is explored, as is the large Ormond estate across Kilkenny and Tipperary, which demonstrated the varying levels of destruction and disruption to normal life caused by the war in different areas. These case studies are complemented by an analysis of the hearth tax records for each county over a twenty-year period, which help to quantify the significant regional impact caused by the Williamite war on the people of Ireland.
Embargo End Date: 2022-01-01
Keywords: Histories & Humanities, Ph.D.; Ph.D. Trinity College Dublin, 2013